Meningkatkan Hasil Belajar Matematika melalui Penerapan Pembelajaran Kooperatif Tipe Think Pair Share pada Siswa Kelas VII B SMP Negeri 10 Ujung Loe Kabupaten Bulukumba - Muhammad Awal Nur (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2017)
This research is a classroom action research that aims to know the improvement of mathematics learning outcomes through the application of Think-Pair-Share Cooperative Learning (TPS). The subjects of this study were students of Class VII B SMP Negeri 10 Ujung Loe Kab. Bulukumba in the odd semester of the academic year 2016/2017, with a total of 30 students, consisting of 15 men and 15 women. This classroom action procedure takes 2 cycles. Cycle I held 4 meetings and Cycle II held 4 meetings. Data collection is done by using learning result test and observation. The collected data were analyzed by using qualitative analysis and quantitative analysis. The result of this research showed that quantitative improvement of mathematics learning outcomes after the implementation of Think-Pair-Share (TPS) cooperative learning, in cycle I showed that the average of student's learning result was 39,50 from ideal score that might be reached 100, Standard deviation of 24.58 and is in the low category. There are 7 complete students (23,33%) and 23 students (76,67%), and in cycle II shows the average of student's learning result is 69,50 from ideal score that might be reached 100, standard Deviation of 24.99 and is in the high category. There are 21 complete students (70%) and 9 (30%) unfinished students. While qualitatively during the learning process takes place changes in student attitudes. This is marked by the increased activity and activity of students during the implementation of the teaching took place viewed from the observation sheet conducted during the study. From the analysis can be concluded that with the implementation of cooperative learning type Think-Pair-Share (TPS) there is an increase in the results of learning mathematics students of class VII B SMP Negeri 10 Ujung Loe Bulukumba